2016
DOI: 10.1007/s11032-016-0481-z
|View full text |Cite
|
Sign up to set email alerts
|

Genetic analysis of NEKODE1 gene involved in panicle branching of foxtail millet, Setaria italica (L.) P. Beauv., and mapping by using QTL-seq

Abstract: We carried out genetic analysis and map

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…High-throughput genotyping by sequencing is an option for efficient marker-assisted breeding [ 45 ]. Currently, there are many new methods using NGS for identifying genes or QTLs, including GWAS [ 46 ], QTL-seq [ 47 ], MutMap [ 48 ], RAD-seq [ 35 ], and SLAF-seq [ 49 ], and some have been applied to foxtail millet [ 15 , 30 , 31 ]. However, the utility of RAD-seq has yet not been reported.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…High-throughput genotyping by sequencing is an option for efficient marker-assisted breeding [ 45 ]. Currently, there are many new methods using NGS for identifying genes or QTLs, including GWAS [ 46 ], QTL-seq [ 47 ], MutMap [ 48 ], RAD-seq [ 35 ], and SLAF-seq [ 49 ], and some have been applied to foxtail millet [ 15 , 30 , 31 ]. However, the utility of RAD-seq has yet not been reported.…”
Section: Resultsmentioning
confidence: 99%
“…Bai et al [ 15 ] re-sequenced the foxtail millet landrace ‘Shi-Li-Xiang’ (SLX) and finely mapped a waxy gene using newly developed DNA markers. Masumot et al [ 31 ] carried out QTL-seq and rapidly mapped the NEKODE1 gene responsible for tip-branched panicle.…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, the use of bulked segregant analysis (BSA) to quickly analyze mutant collections generated by chemical mutagenesis ( Jiang et al, 2017 ) is accelerating Setaria gene discovery ( Xue et al, 2016 ; Fan et al, 2017 ; Huang et al, 2017 ). New genes contributing to leaf color ( Li et al, 2016 ), height, and inflorescence architecture ( Masumoto et al, 2016 ; Huang et al, 2017 ; Xiang et al, 2017 ; Yang et al, 2018 ) have been successfully identified with this approach, substantially advancing our understanding of important traits.…”
Section: Perspectives For Future Breedingmentioning
confidence: 99%
“…Using this method, Li et al (2016) mapped a yellow–green leaf mutation in foxtail millet to a chlorophyll biosynthesis related gene SiYGL1 . Masumoto et al (2016) mapped a branching panicle mutation, a yield related trait in foxtail millet, to a candidate gene NEKODE1 . In chemically induced mutants of S. viridis , BSA can be expected to define causative mutations to a one to few gene interval within two generations (<7 months).…”
Section: Advances Of Forward Genetics In Setaria and Other Milletsmentioning
confidence: 99%